Integrated Global and Local Path Planning for Quadrotor Using Particle Swarm Optimization. Issue 2 (2020) - Hong, Youkyung; Kim, Suseong; Cha, Jihun
Abstract: This study proposes a new path planning method for quadrotors to determine a set of waypoints by considering both geometric constraints to avoid collisions with obstacles and dynamic constraints to reflect the dynamic characteristics of the quadrotor. The proposed path planning method can be formulated as a non-linear optimization problem that minimizes the Euclidean distance between waypoints while satisfying the geometric and dynamic constraints. Particle swarm optimization is utilized to solve the non-linear optimization problem efficiently. By utilizing the Gazebo simulator, the performance of the proposed path planning method is validated for a quadrotor.